Differential effects of small-group and whole-class instructions on primary pupils’ academic achievement in english language (2021)
Achievement is taken as the major goal for which classroom is set up. This is because society frowns at any classroom effort that does not lead to pupils’ high achievement. Hence, the reason society may hold both home and school factors responsible in this regard among others. In order to improve pupils’ academic achievement, educationists continue to encourage teachers to change their methods to bring about quality learning and achievement. This study therefore investigated effects of two different teaching strategies among primary school pupils. The research design employed was the pre-test, post-test control group quasi-experimental design. Two research hypotheses were formulated and tested at 0.05 level of significance. The participants (58 males and 42 females) were drawn from randomly selected primary five classes in public schools in Ibadan North Local Government Area of Oyo State. The instrument used to collect the data was English Language Achievement Test (ELAT). The data collected were analysed using descriptive statistics which includes mean, standard deviation while inferential statistics includes use of t-test. The result revealed significant main effect on pupils' performance on English Language achievement test. However, there was no significant difference in the performance of male and female pupils. Based on the findings, it was recommended that the use of small group instruction should be adopted in primary school to enhance the teaching and learning of English Language among others.